The role of house dust mites in the etiology of Atopic Dermatitis. - Atherton, D.J. (European Journal of Pediatric Dermatology, 2018)
The problem of the relationship between atopic dermatitis and house dust mites is investigated. The data supporting a role of these mites in the pathogenesis of the disease are reviewed. It is unlikely that a sensitisation to mites can initiate atopic dermatitis. On the other hand, it seems more feasible that atopic dermatitis may encourage sensitisation to mites by increasing antigen penetration, and that mites antigens may thereafter aggravate the disease.